(untitled) (Research, Society and Development, 2021)
Objective: to characterize the sociodemographic, clinical and therapeutic profile of two patients, in their first elective surgery for coloretal cancer, as well as the realization of the pre-operative demarcation of the stoma, in a São Paulo public university hospital. Methodology: descriptive, retrospective and cross-sectional study, with a quantitative approach, by means of the collection of medical records, with a data collection instrument on the sociodemographic, clinical and therapeutic profile of patients of the Coloproctology specialty, in their first elective surgery for coloretal cancer. Results: there is a predominance of idosos, with companions, fundamental ensino, settled, location of the tumor in the sigmoid junction, sigmoid and retal challenges, presence of comorbidities and overweight / obesity, moderately differentiated adenocarcinoma, surgeries performed by open surgery, neural hemilemoid surgery / challenges Perform neoadjuvant treatment for all participants to receive stoma pre-operative demarcation. After surgery, 51 (42.1%) patients presented predominantly colostomy, all cross-referenced to a specialized program of the Brazilian Public Health System (SUS). Conclusion: The results show the importance of the systematization of the stoma demarcation, the fundamental aspects that influence the demarcation of the stoma, as well as the clinical assessment, indicating the need for specialized training by two general nurses from hospital institutions on stoma demarcation and fundamental perioperative care for these patients, regarding the prevention of stoma complications and the peristomal skin.